Pemberdayaan Kader Posyandu Dalam Memaksimalkan Promosi Kesehatan Jiwa Masyarakat Kelurahan Samapuin - Lina Eta Safitri; Putri Adekayanti; Abdul Hamid (CV. Aksara Global Akademia, 2024)
Mental health is an important part of overall well-being and health in general. Referring to several previous research, it shows that the contribution of cadres has an influence on the Indonesian health service system. With this context, there is a big opportunity for cadres to participate in efforts to treat mental health For this reason, the aim of this community service activity is: Posyandu cadres are expected to be able to protect the community around where they live to help create a good social environment to help accelerate the recovery of PLWH. This service activity was carried out in Samapuin Village, Unter Iwes District, Sumbawa Regency, NTB. Carried out by dividing into small groups using posters as the media. The results obtained are solving problems that occur among ODDP (People with Psychosocial Disabilities) in Samapuin Village and increasing support for a good social environment for ODDP. It is hoped that in the future there will be regular meetings from the Community Health Center to continue empowerment activities for Posyandu cadres related to social environmental support for ODDP.